Carinata growth, yield, and chemical composition responses to nitrogen fertilizer management. (12th October 2020) - Seepaul, Ramdeo; Mulvaney, Michael J.; Small, Ian M.; George, Sheeja; Wright, David L.
Abstract: Production of carinata ( Brassica carinata A. Braun) as a winter crop in the Southeast United States presents a unique opportunity for growers to produce significant amounts of biofuel feedstock to meet domestic energy needs. Field experiments were conducted to quantify the effects of N application rates (0, 45, 90, and 135 kg N ha −1 ) and split management (single, two‐way split, or three‐way split of 90 kg N ha −1 applied at planting, bolting, and flowering) on carinata growth, yield, and chemical composition. In Study 1, plant height, mainstem node numbers, primary and secondary branches, pod length, pods numbers, and seeds per pod increased quadratically with N application rate. Averaged over the 5 yr, seed yield response to N application rate was quadratic and ranged from 1, 245 kg ha −1 with 0 kg N ha −1 to 2, 444 kg ha −1 with 117 kg N ha −1 . The economic optimum nitrogen rate (EONR) occurred at 103 kg N ha –1, which produced 2, 427 kg seed ha −1 representing a US386 ha −1 profit margin. Except for protein, N application rate did not have an effect on glucosinolates and fatty acid composition. In Study 2, a split application of N had variable effects on carinata growth; however, seed yield did not vary with split management or timing of N averaging 3, 905 kg ha −1 . Split management and N source did not have an effect on seed chemical composition. These results suggest that carinata grown at the EONR of 103 kg N ha −1 can maximize seed and oil production in the Southeast.